Catalytic Oligomerization of Isobutyl Alcohol to Hydrocarbon Liquid Fuels over Acidic Zeolite Catalysts. Issue 2 (10th January 2020) - Guo, Xiaoyu; Guo, Lisheng; Suzuki, Yuichi; Wu, Jinhu; Yoneyama, Yoshiharu; Yang, Guohui; Tsubaki, Noritatsu
Abstract: Catalytic isobutyl alcohol oligomerization to generate hydrocarbon liquid fuels over zeolite has been investigated over H−Y, SAPO‐34, H‐MOR zeolite and Al‐MCM‐41 catalysts, as a new way to direct conversion of isobutyl alcohol to hydrocarbon liquid fuels, considering the fact that isobutyl alcohol can be obtained from biomass by microbes. In this study, all of the zeolite samples showed good reactivity, especially H‐MOR, achieving 94 % conversion of isobutyl alcohol and 63 % selectivity of C5+ liquid fuels in all products. The effects of reaction conditions including reaction temperature and reaction time were also discussed. The physicochemical properties of the catalysts were characterized by XRD, Nitrogen adsorption‐desorption, NH3‐TPD, TG/DTA, and GS/MS. The reaction system discussed here involves two reactions, i) isobutyl alcohol dehydration reaction via a typical acid catalysis, ii) a polymerization reaction of small molecules into large ones, according to the experimental and characterization results, the pore size and acid property of the zeolite are the two main factors controlling this catalytic dehydration and oligomerization reaction. Abstract : A new way of one‐step produces the liquid fuels from isobutyl alcohol by using the acidic sites of the zeolite. By comparison of the H−Y, SAPO‐34, H‐MOR zeolite and Al‐MCM‐41 catalysts, find that during the isobutyl alcohol oligomerization reaction, different catalysts shows the different dehydration and oligomerization behavior, only the H‐MOR shows the ability of both dehydration and oligomeriztion reaction.